Electrochemical synthesis and study of polyanilines with covalently attached acidic groups - Gutić, Sanjin (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Explores electrochemical copolymerization of aniline with acid and hydroxyl derivatives, examining pH-dependent redox properties and electrical characteristics of resulting films through voltammetric and impedance methods.